The impact of distraction minimization on endoscopic mentoring and performance - Rice, Sean C.; Slaughter, James C.; Smalley, Walter; Obstein, Keith L. (Endoscopy International Open, 2020)
Background and study aims Endoscopic mentoring requires active attention by the preceptor. Unfortunately, sources of distraction are abundant during endoscopic precepting. The impact of distraction minimization on endoscopic mentoring and performance is unknown.Methods Fellow and attending preceptors were paired and randomized in a prospective crossover design to perform esophagogastroduodenoscopy (EGD) and/or colonoscopy in either a “distraction minimization” (DM) or a “standard” (S) room. Cell phones, pagers, music, and computers were not permitted in DM rooms. S rooms operated under typical conditions. Fellows and attendings then completed a survey. The primary outcome was fellow satisfaction with mentoring experience (visual analogue scale: 0 = min,100 = max). Additional fellow outcomes included satisfaction of attending attentiveness, identifying landmarks, communication, and distractedness; attending outcomes included satisfaction with mentoring, attentiveness, communication, and distractedness. Endoscopic performance measures included completion of EGD, cecal intubation rate, cecal intubation time, withdrawal time, total procedure time, attending assistance, and polyp detection rate. A paired t-test was used to compare mean differences (MD) between rooms; significance set at P < 0.05. Results Eight fellows and seven attendings completed 164 procedures. Despite a trend toward less distraction between rooms (DM = 12.5 v. S = 18.3, MD =  4.1, P = 0.17), there was no difference in fellow satisfaction with training/mentoring (DM = 93, S = 93, MD = –0.04, P = 0.97), attentiveness (DM = 95, S = 92, MD = 0.86, P = 0.77), identifying pathology/landmarks (DM = 94, S = 94, MD = –1.72, P = 0.56), or communication (DM = 95, S = 95,MD = 1.0, P = 0.37). Similarly, there was no difference between rooms for any attending outcome measures or performance metrics. Conclusions DM did not improve perceived quality of endoscopic mentoring or performance for fellows or attendings; however, reduced distraction may improve attending engagement/availability.